Тhe system of Еuro-Аtlantic security in the conditions of modern military-political conflict on Еast Еurope - Hrubinko, Andrii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
In the article the problems of development the system of Euro-Atlantic security in the context of the modern intensifying military-political conflict on East Europe in connection with the Russian-Ukrainian conflict are examined. Character of relations between EU and NATO in the field of security and defens is analysed. An author is accent attention on strategic errors, which the states of the West, European Union and United States were admitted in relationship with Russia since stopping «cold war» and in a policy to the states of post-soviet area. Forming factors and character political position of EU, USA and NATO during military-political aggression of Russia against Ukraine in 2014 are educed. Prognoses in relation to further development of the system of Euro-Atlantic security are given.